COVID – 19 in two dialysis centers situated in two neighbouring states of the Western Balkans - Enisa Mesic; Mirna Aleckovic-Halilovic; Karolina Paunovic; Alexander Woywodt; Mirha Pjanic; Goran Paunovic (BMC Nephrology, 2023)
Abstract Background Bosnia and Herzegovina (BiH) and Serbia are countries in the Western Balkans that share parts of their social and political legacy from the former Yugoslavia, such as their health care system and the fact that they are not members of European Union. There are very scarce data on COVID – 19 pandemic from this region when compared to other parts of the world and even less is known about its impact on the provision of renal care or differences between countries in the Western Balkans. Materials and methods This observational prospective study was conducted in two regional renal centres in BiH and Serbia, during the COVID – 19 pandemic. We obtained demographic and epidemiological data, clinical course and outcomes of dialysis and transplant patients with COVID – 19 in both units. Data were collected a via questionnaire for two consecutive time periods: February – June 2020 with a total number of 767 dialysis and transplant patients in the two centres, and July – December 2020 with a total number of 749 studied patients, corresponding to two of the largest waves of the pandemic in our region. Departmental policies and infection control measures in both units were also recorded and compared. Results For a period of 11 months, from February to December 2020, 82 patients on in-centre haemodialysis (ICHD), 11 peritoneal dialysis patients and 25 transplant patients who tested positive for COVID-19. In the first study period, the incidence of COVID – 19 positive in Tuzla was 1.3% among ICHD patients, and there were no positive peritoneal dialysis patients, or any transplant patients who tested positive. The incidence of COVID-19 was significantly higher in both centres in the second time period, which corresponds to the incidence in general population. Total deaths of COVID-19 positive patients was 0% in Tuzla and 45.5% in Niš during first, and 16.7% in Tuzla and 23.4% in Niš during the second period. There were notable differences in the national and local/departmental approach to the pandemic between the two centres. Conclusion There was poor survival overall when compared to other regions of Europe. We suggest that this reflects the lack of preparedness of both of our medical systems for such situations. In addition, we describe important differences in outcome between the two centres. We emphasize the importance of preventative measures and infection control and highlight the importance of preparedness.